The Fear of Covid-19 and Perceived Employability Effect on Emotional Exhaustion and Work Engagement: The Mediating Role of Job Insecurity - Dewi, Putu Parama Cinthya; Martdianty, Fanny (JDM (Jurnal Dinamika Manajemen), 2023)
Frontline workers are one of the jobs affected due to Covid-19. Covid-19 events can have negative and positive consequences for frontline workers. This study aims to see how fear of covid affects employee emotional exhaustion during a pandemic. Based on the conservation of resources theory, fear of covid-19 can cause frontline workers to experience emotional exhaustion. In addition, during a pandemic, employees can feel high job insecurity, resulting in low work engagement in the company where employees work. The method used in this research is quantitative. Data analysis was performed on 259 company employees who worked as frontline workers using the Structural Equation Modeling technique. The results of the analysis show that fear of covid-19 has a positive effect on job insecurity, and job insecurity has a significant positive effect on emotional exhaustion. In addition, perceived employability has a positive and significant effect on job insecurity and a significant positive effect on work engagement. It is essential for companies to pay attention so that employees do not have high job insecurity and high emotional exhaustion and can create employee work engagement by conducting various kinds of training and health education to increase engagement and reduce employee fear of Covid.